1976
DOI: 10.1111/j.1528-1157.1976.tb03383.x
|View full text |Cite
|
Sign up to set email alerts
|

A Follow‐Up Study of 91 Patients Operated on for Focal Epilepsy

Abstract: Ninety-one patients operated on for focal epilepsy between 1952 and 1973 have been followed regularly. Nontumoral lesions were found in 68 patients, and tumors in 23. Of the 50 patients without tumor who have been followed for more than 2 years, 30% were seizure-free, 50% improved, while only 20% did not benefit from the operation. There was no operative mortality. Ventricular asymmetry in the pneumoencephalogram was associated with a better prognosis than when there was no or symmetrical enlargement. The time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In series with patients followed for 6 months to 10 years, investigators should report separately the results of patients followed for different periods, e.g., 6 months and 1, 2, 5 , and 10 years. Combining results of all patients and reporting on an average follow-up time makes interpretation of the results difficult, (Falconer et al, 1963;Bhatia et al, 1976;Davidson et al, 1975;Jensen, 1975;Rasmussen, 1980;Lindsay et al, 1984;Brey et al, 1985;King et al, 1986). On the other hand, there is no single magic follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…In series with patients followed for 6 months to 10 years, investigators should report separately the results of patients followed for different periods, e.g., 6 months and 1, 2, 5 , and 10 years. Combining results of all patients and reporting on an average follow-up time makes interpretation of the results difficult, (Falconer et al, 1963;Bhatia et al, 1976;Davidson et al, 1975;Jensen, 1975;Rasmussen, 1980;Lindsay et al, 1984;Brey et al, 1985;King et al, 1986). On the other hand, there is no single magic follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies have shown a bivariate connection between duration of seizure disorder and PREDICTING SUCCESSFUL NEUROSURGERY 575 seizure relief (Stepien et al, 1969;Jensen, 1976;Bergen et al, 1984), whereas five studies showed no such connection (Bloom et al, 1959160;Bengzon et al, 1968;Bathia and Kollevold, 1976;Wannamaker and Matthews, 1976;Dodrill et al, 1986). We suspect that one reason why so many studies have failed to show a relation between outcome and duration of seizure disorder is that only linear relations were examined.…”
Section: Duration Of Diseasementioning
confidence: 98%
“…Patients who were unduly apprehensive or under the age of 12-15 years were operated under general anaesthesia. An attempt was made to map the area of maximum epileptogenic activity and excise it without encroaching upon areas likely to cause neurologic deficit (Bathia and Kollevold, 1976).…”
Section: Measurements and Modelmentioning
confidence: 99%
“…An attempt was made to map the area of maximum epileptogenic activity and excise it without encroaching upon areas likely to cause neurologic deficit (Bathia and Kollevold, 1976).…”
Section: Surgical Treatment For Partial Epilepsy Amongmentioning
confidence: 99%
“…At Oslo City Hospital, most procedures were tailored resections (average basolateral length of resection in a sample of 22 patients was 5.6 cm) (Bathia and Kollevold, 1976):…”
Section: Surgical Treatment For Partial Epilepsy Amongmentioning
confidence: 99%